Non-centrosymmetric zinc silicate-graphene based transparent flexible piezoelectric nanogenerator. (July 2020) - Bharti, Dhiraj Kumar; Gupta, Manoj Kumar; Kumar, Rajeev; Sathish, Natarajan; Srivastava, Avanish Kumar
Abstract: Rapid advancement of transparent flexible electronics has great potential for next-generation energy devices for self-powered nanosystems and nanosensors. Here, we present the transparent and flexible piezoelectric lead free zinc silicate (Zn2 SiO4 ) nanorods-graphene based nanogenerators for harvesting mechanical energies for the first time. A simple and cost effective hydrothermal method was used to synthesize the piezoelectric Zn2 SiO4 nanorods with non-centrosymmetricity property. Tetragonal crystal system and dimension of nanorods were investigated using X-ray diffraction spectroscopy and high resolution electron microscopies, respectively. Raman spectra exhibited all characteristic signature peaks of the Zn2 SiO4 nanorods. Piezoelectric properties of grown Zn2 SiO4 nanorods was confirmed and a piezoelectric charge coefficient (d33 ) of about 117 p.m./V was obtained through piezoelectric force microscopy study. A high performance piezoelectric hybrid composite nanogenerator was successfully fabricated using polydimethylsiloxane (PDMS) polymer, Zn2 SiO4 nanorods and CVD grown monolayer graphene sheet. The average piezoelectric output voltage and current density of 5.5 V and 0.50 μA/cm 2 were obtained under very small pressure of 0.15 kgf applied through computer controlled dynamic shaker without applying any external electric poling. The average energy conversion efficiency of the flexible piezoelectric Zn2 SiO4 : PDMS-based device was found to be ≈ 29.10%. The mechanism of high piezoelectric output performance from Zn2 SiO4 nanorods device was discussed and co-related with dielectric, piezoelectric and proper adhesion of graphene sheet with polymer composites. Graphical abstract: Image 1 Highlights: Transparent flexible piezoelectric non-centrosymmetric zinc silicate nanorods-graphene based nanogenerators was developed. Piezoelectric charge coefficient (d33 ) of about 117 p.m./V was obtained through piezoelectric force microscopy study. The average energy conversion efficiency of the flexible piezoelectric Zn2 SiO4 : PDMS-based device was found to be ≈ 29.10%.